The Extracellular Matrix-Derived Biomarkers for Diagnosis, Prognosis, and Personalized Therapy of Malignant Tumors - Petersen, Elena V.; Chudakova, Daria A.; Skorova, Ekaterina Yu.; Anikin, Vladimir; Reshetov, Igor V.; Mynbaev, Ospan A. (Frontiers in Oncology, 2020)
The tumour biomarkers already have proven clinical value and have become an integral part in cancer management and modern translational oncology. The tumour tissue microenvironment (TME), which includes extracellular matrix (ECM), signaling molecules, immune and stromal cells, and adjacent non-timorous tissue, contributes to cancer pathogenesis, thus TME-derived biomarkers have many clinical applications. This review is predominately based on the most recent publications (manuscripts published in a last five years, or seminal publications published earlier) and fills a gap in the current literature on the cancer biomarkers derived from the TME, with particular attention given to the ECM and products of its processing and degradation, ECM-associated extracellular vehicles (EVs), biomechanical characteristics of ECM, and ECM-derived biomarkers predicting response to the therapy including immunotherapy. We discuss the clinical utility of the TME-incorporating three-dimensional in-vitro and ex-vivo cell culture models for personalized therapy. We conclude that ECM is a critical driver of malignancies and ECM-derived biomarkers should be included in diagnostics and prognostics panels of markers in the clinic.